The Trades and Labor Congress of Canada and Political Action 1898-1908 - Robin, Martin (Relations industrielles / Industrial Relations, 1967)
An examination of the politics of the Trades and Labour Congress of Canada and its relationship with the radical political movement in English-speaking Canada between 1898 and 1908. The Congress moved left in the years around the turn of the Century and supported the principle of independent labour representation but refrained from endorsing the new Socialist movement. A Canadian Labour Party was launched in 1906 but socialists and independent laborities in the Congress remained unreconciled and the new party failed to get off the ground.